2020
DOI: 10.20535/2410-8286.215117
|View full text |Cite
|
Sign up to set email alerts
|

Use of Task-Based Approach in Teaching Vocabulary to Business English Learners at University

Abstract: The purpose of this study is to identify the effectiveness of the task-based approach to teaching business vocabulary to master's degree students while studying business English. The discipline of business English aims to develop students' ability to analyse and solve problems of the business environment, improve their foreign language competence on the basis of acquired business vocabulary. The authors used the task-based approach in teaching business vocabulary which was aimed at encouraging students to soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In their study, similarly to our research, the students' achievements were statistically more significant in the PBL group than in the traditional learning group. Similar findings were also reported by Nychkalo, Jinba, Lukianova, Paziura and Muranova [22] who revealed a significant positive dynamic in the acquisition of business vocabulary by technical university students that studied ESP using PBL method. Our results are also in line with those obtained by Bicer, Boedeker, Capraro and Capraro [23] who achieved a statistically significant improvement in mathematical, scientific, and environment-related vocabulary acquisition by students in PBL.…”
Section: Discussionsupporting
confidence: 88%
“…In their study, similarly to our research, the students' achievements were statistically more significant in the PBL group than in the traditional learning group. Similar findings were also reported by Nychkalo, Jinba, Lukianova, Paziura and Muranova [22] who revealed a significant positive dynamic in the acquisition of business vocabulary by technical university students that studied ESP using PBL method. Our results are also in line with those obtained by Bicer, Boedeker, Capraro and Capraro [23] who achieved a statistically significant improvement in mathematical, scientific, and environment-related vocabulary acquisition by students in PBL.…”
Section: Discussionsupporting
confidence: 88%
“…The next study by Nychkalo et al (2020) identified the effectiveness of the task-based approach to teaching business vocabulary. In this study, the researchers used different task types for the experimental group during TBI and assessed the students multiple times with aim of solving real business problems, which developed their teamwork and communication skills in a real-life situation.…”
Section: The Empirical Studies About Vocabulary Assessment In Interna...mentioning
confidence: 99%
“…Learning methods such as lectures, question and answer sessions, and group discussions are utilized often in education today (Volpe et al, 2011). There are still some students who, although participating in English learning activities, particularly vocabulary, have a limited ability to say words in accordance with what they say (Nychkalo et al, 2020). Because of these issues, the researchers have an interest in employing or making use of the drill practice to provide students with the opportunity to exercise what they have learned on multiple occasions to improve their skills and dexterity.…”
Section: Introductionmentioning
confidence: 99%